Optimization cutting parameters when grinding X12M steel using Hai Duong grinding wheel - Van Thien, Nguyen; Tien Dung, Hoang; Duc Trung, Do; Cuong, Ngo (International Journal of Engineering and Technology, 2019)
This paper presents an experimental research to build two regressions they are relationship between surface roughness of workpiece and cutting parameters when grinding grinding X12M steel using Hai Duong grinding wheels. Two types of Hai Duong grinding wheel using in this paper are Cn46.TB1.G. V1.400x40x203x50m/s and Cn46.CV1.G. V1.400x40x203x35m/s. Three cutting parameters are considered in this paper are depth of cut, feed rate and velocity of workpiece. Genetic algorithm had used to find value of cutting parameters for minimum value of surface roughness. This work had get optimization value of cutting parameters for each case of a pair of workpiece â€“ wheel.Â Â